The effect of cigarette prices and income on cigarettes consumption and state revenue: Case study of 33 provinces in Indonesia - Arief Tirtana; I Gede Agus Ariutama (Jurnal Ekonomi dan Bisnis, 2022)
Besides having a destructive impact on smokers, cigarette consumption also creates a negative externality for passive smokers. Thus, the government implements cigarette excise to control cigarette consumption while increasing state revenue. This study aims to determine the effect of cigarette prices and income on cigarette consumption and the impact of excise tariffs on cigarette consumption and excise tax revenue. The data used are 33 provincial data in Indonesia from 2013 to 2018. The methods in this research are panel data regression using fixed-effect with GLS for model one and a random effect for model two. The results indicated that the cigarette price elasticity and income elasticity of demand were -0.317 and 0.635, respectively, showing that cigarette consumption is inelastic. In the simulation, an increase in excise tariffs by 10%, 25%, and 50%, respectively, led to a decrease in cigarette consumption by 1.55%, 3.86%, and 7.73%, and an increase in state revenue from excise by 8.3%, 20.17%, and 38.41%. It can be concluded that an increase in cigarette excise rates causes an increase in cigarette prices, leading to a decrease in cigarette consumption. Furthermore, the decline in cigarette consumption increased state revenues from excise.